Substrate for supporting catalyst for exhaust gas purification

CN118401305BActive Publication Date: 2026-10-23NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280082533.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-16
Filing Date
2022-12-14
Publication Date
2026-10-23
Estimated Expiration
2042-12-14

AI Technical Summary

Technical Problem

[0004]然而,在专利文献1和专利文献2所公开的蜂窝体中,孔设置于整个箔,因此压强损失增加

Benefits of technology

[0026]根据本发明的催化剂负载用基材,能够实现:(1)提高净化性能;(2)抑制压强损失的增加;以及(3)抑制开口区域与非开口区域的边界部的断裂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118401305B_ABST
    Figure CN118401305B_ABST
Patent Text Reader

Abstract

The present invention aims to provide a catalyst-supporting substrate that can achieve (1) improved purification performance, (2) suppression of an increase in pressure loss, and (3) suppression of breakage at the boundary between the open region and the non-open region. A catalyst-supporting substrate composed of a plurality of honeycomb bodies for purifying exhaust gas of a vehicle, characterized in that the plurality of honeycomb bodies are arranged with the central axes of the respective honeycomb bodies being substantially uniform, a through-hole is formed in one or more metal foils of a first honeycomb body arranged at a position closest to an exhaust gas inlet side among the plurality of honeycomb bodies, and no through-hole is formed in the metal foils of the remaining one or more honeycomb bodies, in the case where the first honeycomb body is divided into an open region in which the through-hole is formed, a first non-open region from an exhaust gas inlet side end portion of the open region to an exhaust gas inlet side edge portion of the first honeycomb body, and a second non-open region from an exhaust gas outlet side end portion of the open region to an exhaust gas outlet side edge portion of the first honeycomb body in the axial direction, the length of the first non-open region in the axial direction is 2 mm or more and 10 mm or less, the length of the second non-open region in the axial direction is 10 mm or less, in the axial direction, a honeycomb body adjacent to the first honeycomb body is defined as a second honeycomb body, the first honeycomb body and the second honeycomb body are separated in the axial direction, the separation distance of the first honeycomb body and the second honeycomb body in the axial direction is 2 mm or more and 20 mm or less, and the proportion of the axial length of the open region with respect to the sum of the axial lengths of the plurality of honeycomb bodies is 20% or more and 80% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a catalyst-supported substrate for purifying air pollutants and the like contained in exhaust gases. Background Technology

[0002] As a purification device for purifying exhaust gases from an internal combustion engine, a catalytic converter is known, which consists of a metal honeycomb structure (a catalyst-supporting substrate) embedded in a heat-resistant alloy outer cylinder. By placing the catalytic converter in the exhaust gas path, the exhaust gas passing through the catalytic converter comes into contact with the catalyst over a large area, thus achieving efficient purification of the exhaust gas. As the aforementioned honeycomb structure, honeycombs formed by alternately stacking flat metal foils and corrugated foils (made by corrugating the flat metal foils), or honeycombs formed by winding flat metal foils and corrugated foils, are examples.

[0003] To improve the purification performance of exhaust gas in catalytic converters, a honeycomb structure with holes throughout the foil has been proposed (see Patent Documents 1 and 2). By forming holes in the foil, it is possible to: (A) reduce the heat capacity of the honeycomb structure, thus enabling earlier activation of the catalyst loaded in the honeycomb structure by utilizing the heat of the exhaust gas; and (B) facilitate turbulence of the exhaust gas passing through the honeycomb structure, enabling more efficient purification of the exhaust gas. Therefore, the purification performance of the honeycomb structure can be improved.

[0004] However, in the honeycomb structures disclosed in Patent Documents 1 and 2, the holes are arranged throughout the foil, thus increasing the pressure loss.

[0005] In view of this, Patent Document 3 proposes a metal carrier (honeycomb) with openings only on the upstream side of the exhaust gas path in the flat foil and / or corrugated foil of the honeycomb structure. In the metal carrier, the portion of the exhaust gas at the early contact point with the heated exhaust gas contributes significantly to the early activation of the catalyst. Therefore, by providing openings on the upstream side of the exhaust gas path, the effect of early catalyst activation described in (A) above can be fully utilized. Furthermore, as explained in (B) above, forming openings on the foil facilitates turbulence of the exhaust gas. Therefore, the purification performance can be improved according to the structure disclosed in Patent Document 3. Moreover, by adopting a structure without openings on the downstream side of the exhaust gas path, the increase in pressure loss, which is a technical problem in Patent Documents 1 and 2, can be suppressed.

[0006] Prior art literature

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 55-132640;

[0009] Patent Document 2: Japanese Patent Application Publication No. 62-53744;

[0010] Patent Document 3: Japanese Patent Application Publication No. 6-320014;

[0011] Patent Document 4: International Publication No. 90-03842;

[0012] Patent document 5: Japanese Patent Application Publication No. 2011-156505;

[0013] Patent Document 6: Japanese Utility Model Application Publication No. 2-83320;

[0014] Patent document 7: Japanese Patent Application Publication No. 5-195763. Summary of the Invention

[0015] The technical problem that the invention aims to solve

[0016] However, a durability test based on exhaust gas conduction was conducted on the metal carrier proposed in Patent Document 3. The results confirmed that cracks and metal carrier breakage occurred at the boundary between the area with an opening (hereinafter referred to as the open area) and the area without an opening (hereinafter referred to as the non-open area) in the metal carrier.

[0017] Therefore, the object of the present invention is to provide a catalyst-supported substrate that can achieve: (1) improved purification performance; (2) suppression of increased pressure loss; and (3) suppression of breakage at the boundary between the open and non-open regions.

[0018] Technical means to solve technical problems

[0019] To solve the above-mentioned technical problems, the present invention provides:

[0020] (1) A catalyst support substrate, comprising a plurality of honeycomb cells, for purifying vehicle exhaust gas, characterized in that the plurality of honeycomb cells are arranged in a manner in which the central axes of each honeycomb cell are substantially aligned; a plurality of through holes are formed on the metal foil of the first honeycomb cell located closest to the exhaust gas inlet side; no through holes are formed on the metal foil of the remaining honeycomb cells; the first honeycomb cell is axially divided into an open region having the through holes, a first non-open region extending from the exhaust gas inlet side end of the open region to the exhaust gas inlet side edge of the first honeycomb cell, and an exhaust gas outlet side end of the open region. The second non-opening region extends to the exhaust outlet side edge of the first honeycomb cell. At this time, the length of the first non-opening region along the axial direction is more than 2 mm and less than 10 mm, and the length of the second non-opening region along the axial direction is less than 10 mm. In the axial direction, the honeycomb cell adjacent to the first honeycomb cell is defined as the second honeycomb cell. At this time, the first honeycomb cell and the second honeycomb cell are separated in the axial direction, and the separation distance between the first honeycomb cell and the second honeycomb cell in the axial direction is more than 2 mm and less than 20 mm. The ratio of the axial length of the opening region to the sum of the axial lengths of the plurality of honeycomb cells is more than 20% and less than 80%.

[0021] (2) The catalyst-supported substrate according to (1) is characterized in that the axial separation distance between the first honeycomb and the second honeycomb is more than 2 mm and less than 10 mm.

[0022] (3) The catalyst-supported substrate according to (1) or (2) is characterized in that the length of the second non-opening region along the axial direction is longer than the length of the first non-opening region along the axial direction.

[0023] (4) A honeycomb cell, characterized in that it comprises: a catalyst-supported substrate as described in any one of (1) to (3); and an outer cylinder that houses the catalyst-supported substrate.

[0024] (5) A catalytic converter, characterized in that it comprises: (4) the honeycomb unit; and a catalyst supported on the plurality of honeycomb units.

[0025] Beneficial effects

[0026] The catalyst-supported substrate according to the present invention can achieve: (1) improved purification performance; (2) suppression of increased pressure loss; and (3) suppression of breakage at the boundary between the open and non-open regions. Attached Figure Description

[0027] Figure 1 This is a perspective view of the cellular unit in this embodiment.

[0028] Figure 2 yes Figure 1 The image shows a longitudinal sectional view of a cellular cell.

[0029] Figure 3 yes Figure 1 The enlarged longitudinal section view of the first honeycomb cell 4A shown.

[0030] Figure 4 yes Figure 1 The unfolded diagram of the flat foil 2 in the first honeycomb body 4A shown.

[0031] Figure 5 yes Figure 4 An enlarged view of the region S enclosed by the dashed line.

[0032] Explanation of reference numerals in the attached figures

[0033] 1: Cellular Unit

[0034] 2: Flat foil

[0035] 3: Corrugated foil

[0036] 4: Catalyst Support Substrate

[0037] 4A: First honeycomb

[0038] 4B: Second honeycomb

[0039] 5: Outer cylinder

[0040] 6: Separation section

[0041] 41: Opening area

[0042] 44: First non-opening area

[0043] 45: Second non-opening area

[0044] 46: Non-opening area

[0045] 410: Through hole Detailed Implementation

[0046] (Basic structure of a cellular unit)

[0047] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. Figure 1 This is a perspective view of the cellular unit in this embodiment. Figure 2 yes Figure 1 The image shows a longitudinal sectional view of a cellular cell. Figure 2 The arrow shown indicates the direction of exhaust gas flow, which is aligned with the axial direction of the catalyst-supported substrate. (Refer to...) Figure 1 and Figure 2The honeycomb cell 1 includes a catalyst-supporting substrate 4 and a heat-resistant metal outer cylinder 5 for housing the catalyst-supporting substrate 4. In this embodiment, the catalyst-supporting substrate 4 has a structure in which a first honeycomb cell 4A disposed on the upstream side of the exhaust gas path and a second honeycomb cell 4B disposed on the downstream side of the exhaust gas path, substantially aligned with the central axis of the first honeycomb cell 4A and adjacent to the first honeycomb cell 4A in the axial direction, are arranged in series. However, one or more honeycomb cells having the same structure as the second honeycomb cell 4B may be further arranged in series on the downstream side of the second honeycomb cell 2B. "Substantially aligned with the central axis" means that not only is complete overlap of the central axis allowed, but also some deviations caused by manufacturing errors of the honeycomb cells are allowed. The cell density of the first honeycomb cell 4A and the second honeycomb cell 4B is preferably set to 100 to 600 channels per square inch. Increasing the cell density improves the purification performance, but also increases the pressure loss. Therefore, the set cell density value can be appropriately selected according to the required output performance and the grade of the exhaust gas.

[0048] The first honeycomb cell 4A and the second honeycomb cell 4B are constructed by winding flat foil 2 and corrugated foil 3 made of heat-resistant alloy around an axis in an overlapping state, and then joining the flat foil 2 and corrugated foil 3 together with solder. Therefore, the flat foil 2 and corrugated foil 3 are alternately stacked in the radial direction. According to the above structure, multiple axially extending gas flow paths can be formed inside the first honeycomb cell 4A and the second honeycomb cell 4B. Furthermore, the corrugated foil 3 is formed by corrugating the flat foil 2. The first honeycomb cell 4A and the second honeycomb cell 4B are inserted into the outer cylinder 5, and the outermost peripheral surfaces of the first honeycomb cell 4A and the second honeycomb cell 4B are joined to the inner peripheral surface of the outer cylinder 5 using solder, thereby forming the honeycomb unit 1. The joining positions of the flat foil 2 and the corrugated foil 3, and the joining positions of the first honeycomb cell 4A, the second honeycomb cell 4B, and the outer cylinder 5 are not particularly limited; for example, they can be joined at known joining positions shown in Patent Documents 4 and 5. For the bonding of the flat foil 2 and the corrugated foil 3, and for the bonding of the first honeycomb body 4A, the second honeycomb body 4B, and the outer cylinder 5, foil solders can be used, such as nickel-based solders like BNi-2 and BNi-5. However, powdered or granular solders, which are different from foil solders, can also be used.

[0049] The heat-resistant alloy used in the flat foil 2 and the corrugated foil 3 can be a Fe-20Cr-5Al stainless steel, but is not limited to this; various heat-resistant stainless steels containing Al can be used in the alloy composition. Typically, alloys containing 15–25% by mass of Cr and 2–8% by mass of Al can be used as the heat-resistant alloy. For example, Fe-20Cr-5Al alloy, Fe-18Cr-3Al alloy, Fe-20Cr-8Al alloy, etc., can be used. Furthermore, by thinning the foil thickness of the flat foil 2 and the corrugated foil 3, the heat capacity of the honeycomb structure is reduced, thus enabling earlier catalyst activation and further improving initial purification performance. On the other hand, if the foil thickness of the flat foil 2 and the corrugated foil 3 is reduced, the foil strength decreases, thereby reducing the durability of the honeycomb structure. Therefore, the foil thickness of the flat foil 2 and the corrugated foil 3 can be appropriately set based on the required durability and purification performance. Preferably, the foil thickness of the flat foil 2 and the corrugated foil 3 is set to 20 μm to 100 μm. The heat-resistant alloy used for the outer cylinder 5 can be, for example, stainless steel such as SUS436L, but is not limited to this; various heat-resistant alloys can be used. Furthermore, the thickness of the outer cylinder 5 is preferably set to 1mm to 2mm.

[0050] A catalyst (not shown) is loaded onto the flat foil 2 and the corrugated foil 3. The catalyst can be loaded onto the flat foil 2 and the corrugated foil 3 by coating the foil surfaces of the first honeycomb body 4A and the second honeycomb body 4B with a specified coating solution, followed by drying and firing. As a carrier coating solution, for example, a slurry-like substance prepared by stirring γ-alumina powder, lanthanum oxide, zirconium oxide, and cerium oxide in an aqueous solution of palladium nitrate can be used.

[0051] A catalyst-loaded honeycomb unit (i.e., a catalytic converter) can be installed in the vehicle's exhaust path such that exhaust gas flowing in from the inlet end 1A and exiting from the outlet end 1B. Vehicles include two-wheeled vehicles, four-wheeled vehicles, and off-road vehicles. If the exhaust gas flowing into the honeycomb gas flow path comes into contact with the catalyst, CO, hydrocarbons, and NO contained in the exhaust gas will be released. X It is rendered harmless and can release clean gases outside the vehicle.

[0052] (The composition of the first and second honeycomb cells)

[0053] Figure 3 yes Figure 1 The enlarged longitudinal section view of the first honeycomb cell 4A shown. Figure 4 yes Figure 1 The unfolded diagram of the flat foil 2 in the first honeycomb body 4A shown. Figure 4 The direction of exhaust gas conduction shown corresponds to the short side direction of flat foil 2. Figure 4 The circumferential direction of the first honeycomb structure shown corresponds to the long side direction of the flat foil 2. (Refer to...) Figure 4In the first honeycomb body 4A, the flat foil 2 and the corrugated foil 3 are pre-set with multiple through holes 410 in the foil thickness direction at corresponding positions in the exhaust gas conduction direction (the short side direction of the flat foil 2 and the corrugated foil 3). By winding the flat foil 2 and the corrugated foil 3 around the axis in an overlapping state, a region (opening region 41) with through holes 410 in the axial direction is formed in the first honeycomb body 4A (refer to...). Figure 2 , Figure 3 In this embodiment, the through hole 410 is located at a position away from the two edges in the short side direction of the flat foil 2 and the corrugated foil 3 (see reference). Figure 4 That is, in the first honeycomb body 4A, non-opening regions 46 without through holes 410 are formed before and after the axial opening region 41. The non-opening regions 46 are composed of a first non-opening region 44 extending from the inlet side end of the opening region 41 to the inlet side edge of the first honeycomb body 4A and a second non-opening region 45 extending from the outlet side end of the opening region 41 to the outlet side edge of the first honeycomb body 4A. In this embodiment, "the inlet side end of the opening region 41" refers to the interface P that is orthogonal to the axial direction of the first honeycomb body 4A through the outer edge of the through hole 410 formed at the position closest to the inlet side edge of the first honeycomb body 4A, and "the outlet side end of the opening region 41" refers to the interface Q that is orthogonal to the axial direction of the first honeycomb body 4A through the outer edge of the through hole 410 formed at the position closest to the outlet side edge of the first honeycomb body 4A. That is, the region in the first honeycomb 4A sandwiched between interfaces P and Q is the open region 41, the region on the inlet side edge of the first honeycomb 4A that is closer to interface P is the first non-open region 44, and the region on the outlet side edge of the first honeycomb 4A that is closer to interface Q is the second non-open region 45. Figure 3 The interfaces P and Q of the first honeycomb cell 4A are respectively equivalent to Figure 4 P' and Q' are indicated by a single dotted line. Furthermore, by providing a first non-opening region 44 at the inlet-side edge of the first honeycomb cell 4A, damage to the foil of the first honeycomb cell 4A caused by exhaust gas pulsation can be further suppressed.

[0054] Reference Figure 4In this embodiment, the through holes 410 are arranged in a staggered pattern along the axial direction. Here, "staggered" means that the arrangement of the next row of through holes is continuous in the axial direction along an imaginary line extending axially from the midpoint of adjacent circumferential through holes. However, the arrangement of the through holes 410 is not limited to a staggered arrangement along the axial direction; for example, it can also be a matrix arrangement in which the through holes are arranged in a straight line along the axial direction and the circumference of the first honeycomb. Furthermore, the through holes 410 can also be a structure provided only in either the flat foil 2 or the corrugated foil 3. Further, the positions of the through holes 410 provided in the flat foil 2 and the positions of the through holes 410 provided in the corrugated foil 3 can also be different in the exhaust gas conduction direction.

[0055] The diameter (i.e., opening area) and shape of the through-holes 410 can be appropriately set according to the width and length of the flat foil 2 and the corrugated foil 3. The diameter of the through-holes 410 is preferably set to 0.2 mm or more and 8 mm or less. By setting the diameter of the through-holes 410 to 0.2 mm or more, the possibility of the through-holes 410 being blocked by the catalyst can be reduced, thus making it easier to generate turbulence in the exhaust gas and purifying the exhaust gas more efficiently. By setting the diameter of the through-holes 410 to 8 mm or less, the through-holes 410 are moderately smaller, thus making it easier to generate turbulence in the exhaust gas and purifying the exhaust gas more efficiently. Since the through-holes 410 are circular, a suitable opening area for each through-hole 410 is 0.031 mm². 2 Above and 50.3mm 2 Below. Furthermore, as long as the opening area of ​​each through hole 410 is 0.031 mm... 2 Above and 50.3mm 2 The same effect can be achieved even with shapes other than circles (e.g., ellipses).

[0056] (The process of discovering this invention)

[0057] First, the inventors conducted an in-depth study on the mechanism of cracking at the boundary between the open and non-open areas in the metal carrier of Patent Document 3. The results showed that the actual heat capacity and thermal conductivity differ between the open and non-open areas, leading to a larger axial temperature gradient near the boundary, resulting in stress concentration and fracture. Based on this mechanism, the inventors conducted repeated in-depth research and conceived a structure consisting of a front section with an open area and a rear section without an open area. This structure achieves the same "improved purification performance" and "suppression of increased pressure loss" effects as the metal carrier disclosed in Patent Document 3, and reduces the axial temperature gradient near the boundary between the open and non-open areas, thus suppressing cracking at this boundary.

[0058] Here, even if the catalyst support substrate 4 is composed solely of the first honeycomb cell 4A, the axial temperature gradient near the boundary between the open and non-open regions can be reduced, thus suppressing the aforementioned cracking. However, in this structure, for example, compared to the metal carrier described in Patent Document 3, the axial length of the catalyst support substrate 4 cannot be sufficiently ensured. Therefore, the absolute amount of catalyst supported on the catalyst support substrate 4 is insufficient, and the stable purification performance (purification performance after the initial stage) of the honeycomb unit 1 is reduced. It is also possible to ensure the axial length of the catalyst support substrate 4 sufficiently by making the axial length of the first honeycomb cell 4A too long, but in this structure, as described above, while the purification performance is improved, the pressure loss increases. In contrast, by setting the structure of the present invention as described above (a structure having a first honeycomb cell 4A with an open region in the front section and a second honeycomb cell 4B without an open region in the rear section), it is possible to achieve: (1) the axial length of the catalyst support substrate 4 is sufficiently ensured, thus improving the stable purification performance of the honeycomb unit 1, and (2) the axial length of the first honeycomb cell 4A is not too long, thus suppressing the increase in pressure loss. Furthermore, the inventors have also discovered that the presence or absence of through holes relative to the second honeycomb 4B has almost no effect on the initial purification performance of the honeycomb cell 1.

[0059] Given the above process, in the first honeycomb structure 4A, if the axial length T of the first non-opening region 44 is too long, cracks may occur at the boundary P between the opening region 41 and the first non-opening region 44. Furthermore, in the first honeycomb structure 4A, if the axial length B of the second non-opening region 45 is too long, cracks may occur at the boundary Q between the opening region 41 and the second non-opening region 45. Therefore, in the first honeycomb structure 4A, the axial length T of the first non-opening region 44 needs to be set to 2 mm or more and 10 mm or less, and the axial length B of the second non-opening region 45 needs to be set to 10 mm or less. Furthermore, by setting the length of T to 2 mm or more, defects in the foil of the first honeycomb structure 4A caused by exhaust gas pulsation can be suppressed. The lower limit of the axial length B of the second non-opening region 45 is not particularly limited; for example, it can be set to about 1 mm.

[0060] If the ratio of the axial length A of the opening region 41 of the first honeycomb cell 4A to the sum of the axial lengths of each honeycomb cell constituting the catalyst support substrate 4 (in this embodiment, the sum of the axial length L1 of the first honeycomb cell 4A and the axial length L2 of the second honeycomb cell 4B) is set to X, then X is set to 20% or more and 80% or less. If X is less than 20%, the axial length of the opening region 41 becomes too short, and therefore the initial purification performance of the honeycomb cell 1 cannot be sufficiently improved. On the other hand, if X is increased, the axial length of the opening region 41 becomes longer, and therefore the purification performance is improved, but the pressure loss also increases. If X exceeds 80%, the axial length of the opening region 41 becomes too long, and therefore, apart from the pressure loss becoming too large, the purification performance is hardly improved. In this way, the pressure loss and purification performance are inversely related, so the value of X can be appropriately set within the range of 20% or more and 80% or less based on the required output performance and exhaust gas level. Furthermore, X is more preferably set to 25% or more and 55% or less.

[0061] Here, refer to Figure 3 Preferably, the axial length B of the second non-opening region 45 is longer than the axial length T of the first non-opening region 44. According to this structure, when the first honeycomb body 4A is divided into an exhaust gas inlet side region G1 (located at the exhaust gas inlet side) and an exhaust gas outlet side region G2 (located at the exhaust gas outlet side) with its axial center, the opening region 41 is biased towards the exhaust gas inlet side region G1 of the first honeycomb body 4A. Therefore, compared to the exhaust gas outlet side region G2, the heat capacity of the exhaust gas inlet side region G1 can be reduced. Thus, the catalyst can be activated earlier, further improving purification performance. Furthermore, "axial center" corresponds to the interface R that passes through the center of the axial direction of the first honeycomb body 4A and is orthogonal to the axial direction of the first honeycomb body 4A.

[0062] Here, refer to Figure 2 The first honeycomb cell 4A and the second honeycomb cell 4B are arranged axially separated from each other by a separation distance D (mm) on the catalyst-supported substrate 4. The separation distance D (mm) can be appropriately set.

[0063] The separation distance D (mm) is set to 2 ≤ D ≤ 20. The reasoning behind this is explained below.

[0064] When the exhaust gas passes through the catalyst-supported substrate 4, there is a possibility that the flat foil 2 and the corrugated foil 3 may extend due to the heat of the exhaust gas. In this case, if the first honeycomb cell 4A and the second honeycomb cell 4B are too close, they may come into contact and break. Therefore, the separation distance D (mm) is guaranteed to be greater than 2mm.

[0065] On the other hand, when the exhaust gas discharged from the first honeycomb cell 4A flows into the second honeycomb cell 4B, the heat of the exhaust gas diffuses to the outside of the honeycomb cell 1 via the outer cylinder 5 in the separation section 6 between the first honeycomb cell 4A and the second honeycomb cell 4B. Therefore, the temperature of the exhaust gas flowing into the second honeycomb cell 4B is lower than the temperature of the exhaust gas discharged from the first honeycomb cell 4A. The second honeycomb cell 4B is located downstream of the first honeycomb cell 4A, and therefore contributes more to the stable purification performance. However, if the temperature of the exhaust gas flowing into the second honeycomb cell 4B decreases, the activation of the catalyst loaded in the second honeycomb cell 4B is delayed, hindering the improvement of the stable purification performance. By setting the axial length of the separation section 6, i.e., the separation distance D (mm), to 20mm or less, the heat dissipation of the separation section 6 to the outside can be suppressed, and the decrease in the temperature of the exhaust gas flowing into the second honeycomb cell 4B can be suppressed. As a result, the catalyst loaded in the second honeycomb cell 4B can be effectively activated, improving the purification performance.

[0066] The separation distance D (mm) is preferably set to 2 ≤ D < 10. By setting the separation distance D (mm) to less than 10 mm, heat dissipation from the separation section 6 to the outside can be further suppressed, and the decrease in the temperature of the exhaust gas flowing into the second honeycomb cell 4B can be further suppressed. As a result, the catalyst loaded on the second honeycomb cell 4B can be activated more efficiently, further improving the purification performance.

[0067] Conventionally, catalyst-supporting substrates with a structure consisting of two honeycomb cells arranged in series, as disclosed in Patent Documents 6 and 7, use substrates in which no through-holes are formed in the foil of any of the honeycomb cells. In this conventional structure, the exhaust gas flowing into the upstream honeycomb cell flows in a laminar flow (not turbulent) inside the honeycomb cell, thus making it difficult to improve purification performance. To obtain sufficient purification performance using this structure, it is necessary to increase the separation distance between the honeycomb cells. According to this structure, when flowing in the separation section between the upstream and downstream honeycomb cells, turbulence is generated in the exhaust gas, thus improving purification performance in the downstream honeycomb cell. However, as mentioned above, if the separation distance between the honeycomb cells is too large, the heat of the exhaust gas is excessively dissipated through the outer cylinder 5 in the separation section, and the temperature of the exhaust gas flowing into the second honeycomb cell 4B is excessively reduced. In view of these trade-offs, it is generally considered that the separation distance between the honeycomb cells should be set to 10 mm or more and 30 mm or less (see, for example, Patent Document 7).

[0068] On the other hand, as described above, the separation distance D (mm) between the first honeycomb cell 4A and the second honeycomb cell 4B in this invention can be set to less than 10 mm. This is because the first honeycomb cell 4A in this invention is provided with an opening region 41 (a plurality of through holes 410), thus allowing turbulence of the exhaust gas within the first honeycomb cell 4A. Even with a shortened separation distance between the first honeycomb cell 4A and the second honeycomb cell 4B, sufficient purification performance can still be obtained. Therefore, compared to conventional catalyst-supporting substrates that arrange two honeycomb cells without through holes in series, this method achieves a novel effect of further miniaturizing the catalyst-supporting substrate.

[0069] The aperture ratio of the through holes in the opening region 41 can be appropriately set according to the application of the catalyst-supported substrate 4, etc. Here, refer to... Figure 5 The definition of aperture ratio is explained. Figure 5 yes Figure 4 An enlarged view of the region S enclosed by the dashed line. (Refer to...) Figure 5 A triangle is drawn with its vertex at the centroid of the three adjacent through holes 410 (in this embodiment, the center C of the through hole 410). The area of ​​this triangle is defined as the total area, and the area of ​​the portion of the triangle overlapping the through hole is defined as the overlapping area. The aperture ratio is then calculated as the ratio of the overlapping area to the total area. Even if the through hole is not circular, the centroid of the through hole can still be used to define the aperture ratio. Furthermore, even when the through hole configuration is not... Figure 4 In the case of an axially staggered configuration (such as the matrix configuration described above), the aperture ratio can also be calculated according to the above definition.

[0070] Suitablely, the aperture ratio is set to 20% or more and 60% or less. If the aperture ratio is set to 20% or more, the heat capacity of the first honeycomb cell 4A can be moderately reduced, thus improving the initial purification performance more fully. If the aperture ratio is set to 60% or less, the foil in the opening area 41 can be more fully retained, thus further improving the durability of the first honeycomb cell 4A.

[0071] Example

[0072] Next, the invention will be specifically described while showing embodiments. In the embodiments described below, names and symbols correspond to those in the above embodiments.

[0073] In this embodiment, the structural durability, purification performance, and pressure loss were evaluated for a catalytic converter on a catalyst-supported substrate 4 based on the present invention. Tables 1 to 4 show the parameter conditions for each embodiment and comparative example.

[0074] [Table 1]

[0075]

[0076] [Table 2]

[0077] Example 1 36.7% 50μm 300 cpsi 1mm 40% 53mm 140mm 1.5mm Example 2 36.7% 50μm 300 cpsi 1mm 40% 53mm 140mm 1.5mm Example 3 43.2% 50μm 300 cpsi 1mm 40% 53mm 140mm 1.5mm Example 4 36.7% 50μm 300 cpsi 1mm 40% 53mm 140mm 1.5mm Comparative Example 1 36.7% 50μm 300cpsi 1mm 40% 53mm 120mm 1.5mm Comparative Example 2 36.7% 50μm 300 cpsi 1mm 40% 53mm 140mm 1.5mm Comparative Example 3 43.2% 50μm 300 cpsi 1mm 40% 53mm 140mm 1.5mm Comparative Example 4 36.7% 50μm 300cpsi 1mm 40% 53mm 140mm 1.5mm Comparative Example 5 10.1% 50μm 300 cpsi 1mm 40% 53mm 120mm 1.5mm Example 5 20.6% 50μm 300 cpsi 1mm 40% 53mm 120mm 1.5mm Example 6 29.7% 50μm 300 cpsi 1mm 40% 53mm 120mm 1.5mm Example 7 40.1% 50μm 300 cpsi 1mm 40% 53mm 120mm 1.5mm Example 8 50.6% 50μm 300 cpsi 1mm 40% 53mm 120mm 1.5mm Example 9 59.7% 50μm 300 cpsi 1mm 40% 53mm 120mm 1.5mm Example 10 70.1% 50μm 300 cpsi 1mm 40% 53mm 120mm 1.5mm Example 11 79.2% 50μm 300 cpsi 1mm 40% 53mm 120mm 1.5mm Comparative Example 6 89.7% 50μm 300cpsi 1mm 40% 53mm 120mm 1.5mm Comparative Example 7 42.1% 50μm 300 cpsi 1mm 40% 53mm 121mm 1.5mm Example 12 42.1% 50μm 300 cpsi 1mm 40% 53mm 122mm 1.5mm Example 13 42.1% 50μm 300 cpsi 1mm 40% 53mm 125mm 1.5mm Example 14 42.1% 50μm 300 cpsi 1mm 40% 53mm 130mm 1.5mm Example 15 42.1% 50μm 300 cpsi 1mm 40% 53mm 140mm 1.5mm Comparative Example 8 42.1% 50μm 300 cpsi 1mm 40% 53mm 150mm 1.5mm Comparative Example 9 42.1% 50μm 300 cpsi 1mm 40% 53mm 170mm 1.5mm Example 16 44.0% 50μm 300 cpsi 1mm 40% 53mm 120mm 1.5mm Example 17 44.0% 50μm 300 cpsi 1mm 40% 53mm 120mm 1.5mm Example 18 36.4% 50μm 300 cpsi 2mm 40% 53mm 140mm 1.5mm Example 19 43.0% 50μm 300 cpsi 2mm 40% 53mm 140mm 1.5mm Example 20 36.4% 50μm 300 cpsi 2mm 40% 53mm 140mm 1.5mm Comparative Example 10 36.4% 50μm 300 cpsi 2mm 40% 53mm 140mm 1.5mm Comparative Example 11 43.0% 50μm 300 cpsi 2mm 40% 53mm 140mm 1.5mm Comparative Example 12 36.4% 50μm 300 cpsi 2mm 40% 53mm 140mm 1.5mm

[0078] [Table 3]

[0079]

[0080] [Table 4]

[0081] Example 21 38.1% 50μm 300 cpsi 4mm 40% 53mm 140mm 1.5mm Example 22 46.8% 50μm 300 cpsi 4mm 40% 53mm 140mm 1.5mm Example 23 38.1% 50μm 300 cpsi 4mm 40% 53mm 140mm 1.5mm Comparative Example 13 33.8% 50μm 300 cpsi 4mm 40% 53mm 140mm 1.5mm Comparative Example 14 46.8% 50μm 300 cpsi 4mm 40% 53mm 140mm 1.5mm Comparative Example 15 33.8% 50μm 300 cpsi 4mm 40% 53mm 140mm 1.5mm Example 24 41.4% 50μm 300 cpsi 8mm 40% 53mm 140mm 1.5mm Example 25 41.4% 50μm 300 cpsi 8mm 40% 53mm 140mm 1.5mm Comparative Example 16 32.7% 50μm 300 cpsi 8mm 40% 53mm 140mm 1.5mm Comparative Example 17 41.4% 50μm 300 cpsi 8mm 40% 53mm 140mm 1.5mm Comparative Example 18 32.7% 50μm 300 cpsi 8mm 40% 53mm 140mm 1.5mm Example 26 34.6% 50μm 300 cpsi 1mm 20% 53mm 140mm 1.5mm Example 27 42.3% 50μm 300 cpsi 1mm 20% 53mm 140mm 1.5mm Example 28 34.6% 50μm 300 cpsi 1mm 20% 53mm 140mm 1.5mm Comparative Example 19 34.6% 50μm 300 cpsi 1mm 20% 53mm 140mm 1.5mm Comparative Example 20 42.3% 50μm 300 cpsi 1mm 20% 53mm 140mm 1.5mm Comparative Example 21 34.6% 50μm 300 cpsi 1mm 20% 53mm 140mm 1.5mm Example 29 36.3% 50μm 300 cpsi 1mm 60% 53mm 140mm 1.5mm Example 30 41.6% 50μm 300 cpsi 1mm 60% 53mm 140mm 1.5mm Example 31 36.3% 50μm 300 cpsi 1mm 60% 53mm 140mm 1.5mm Comparative Example 22 36.3% 50μm 300 cpsi 1mm 60% 53mm 140mm 1.5mm Comparative Example 23 41.6% 50μm 300 cpsi 1mm 60% 53mm 140mm 1.5mm Comparative Example 24 36.3% 50μm 300 cpsi 1mm 60% 53mm 140mm 1.5mm Example 32 36.7% 30μm 400cpsi 1mm 40% 53mm 140mm 1.5mm Example 33 43.2% 30μm 400cpsi 1mm 40% 53mm 140mm 1.5mm Example 34 36.7% 30μm 400cpsi 1mm 40% 53mm 140mm 1.5mm Comparative Example 25 36.7% 30μm 400cpsi 1mm 40% 53mm 140mm 1.5mm Comparative Example 26 43.2% 30μm 400cpsi 1mm 40% 53mm 140mm 1.5mm Comparative Example 27 36.7% 30μm 400cpsi 1mm 40% 53mm 140mm 1.5mm Example 35 29.0% 50μm 300 cpsi 1mm 40% 83mm 100mm 1.5mm Example 36 37.1% 50μm 300 cpsi 1mm 40% 83mm 100mm 1.5mm Example 37 29.0% 50μm 300 cpsi 1mm 40% 83mm 100mm 1.5mm Comparative Example 28 29.0% 50μm 300 cpsi 1mm 40% 83mm 100mm 1.5mm Comparative Example 29 37.1% 50μm 300 cpsi 1mm 40% 83mm 100mm 1.5mm Comparative Example 30 29.0% 50μm 300 cpsi 1mm 40% 83mm 100mm 1.5mm

[0082] <Evaluation of Structural Durability>

[0083] (Examples 1 to 4)

[0084] As Examples 1 to 4, a catalytic converter using the honeycomb cell 1 of the present invention was fabricated as follows. Two Fe-20Cr-5Al stainless steel foils, each 60 mm wide and 50 μm thick, were perforated with holes of 1 mm diameter. The holes were staggered, and the aperture ratio was set to 40%. The perforation was performed such that the axial length T of the first non-perforated region 44, the axial length A of the perforated region 41, and the axial length B of the second non-perforated region 45 were the values ​​described in Examples 1 to 4 as shown in Table 1.

[0085] One of the two foils that underwent perforation processing was used as flat foil 2, and the other was used as corrugated foil 3. The foil used as corrugated foil 3 was corrugated with a channel density of 300 channels per inch. The flat foil 2 and corrugated foil 3 thus made were wound in an overlapping state to obtain a first honeycomb 4A with a diameter of 50 mm, a length of 60 mm, and a channel density of 300 channels per inch.

[0086] On the other hand, a pair of flat foils and corrugated foils, made of Fe-20Cr-5Al stainless steel foil with a width of 60 mm and a thickness of 50 μm and without any perforation, are wound in an overlapping manner to obtain a second honeycomb 4B with a diameter of 50 mm, a length of 60 mm, and a channel density of 300 channels per inch. The corrugation of the corrugated foil is processed using the same method as described above.

[0087] Then, a 20mm wide and 25μm thick foil solder is wound once around the designated positions of the first honeycomb 4A and the second honeycomb 4B. The first honeycomb 4A and the second honeycomb 4B are then inserted into an outer cylinder 5 with a length of 140mm and a thickness of 1.5mm, with the axial separation distance D between them set to 20mm. BNi-5 is used as the foil solder, and SUS436L is used as the outer cylinder. After insertion, the outer diameter of the outer cylinder 5 is reduced to 53mm. Then, powder solder is applied to the designated positions of the first honeycomb 4A and the second honeycomb 4B. BNi-5 is used as the powder solder.

[0088] Regarding the joining structure within the first honeycomb body 4A and the second honeycomb body 4B, and the joining structure between the first honeycomb body 4A, the second honeycomb body 4B, and the outer cylinder 5, the brazing filler metal is applied in a manner that yields the joining structure described in Figure 7 of Patent Document 4. Specifically, both the first honeycomb body 4A and the second honeycomb body 4B have 2 to 3 layers of corrugated foil 2 and flat foil 3 joined from the outermost periphery in a region 10 mm from the gas inlet side end face. Furthermore, the first honeycomb body 4A and the outer cylinder 5 are joined in a region 10 mm from the outlet side edge of the first honeycomb body 4A, and the second honeycomb body 4B and the outer cylinder 5 are joined in a region 10 mm from the outlet side edge of the second honeycomb body 4B.

[0089] Then, a vacuum heat treatment was performed at 1200°C for 10 minutes in a vacuum atmosphere, followed by cooling to obtain the honeycomb unit 1.

[0090] In the first honeycomb cell 4A and the second honeycomb cell 4B of the honeycomb unit 1, a coating solution mainly composed of cerium oxide-zirconium oxide-lanthanum oxide-alumina, containing 1.25g of palladium per 100g, is introduced. After removing excess coating solution, the mixture is dried at 180°C for 1 hour, followed by calcination at 500°C for 2 hours. This results in a coating layer being loaded onto a metal foil with a dry weight of 200g / L per unit volume of the first honeycomb cell 4A and the second honeycomb cell 4B, thus obtaining a catalytic converter. The palladium loading is 2.5g / L.

[0091] (Comparative Example 1)

[0092] As a comparative example 1, a catalytic converter was fabricated as follows. Two Fe-20Cr-5Al stainless steel foils, each 120 mm wide and 50 μm thick, were perforated with holes of 1.0 mm diameter. The holes were staggered, and the aperture ratio was set to 40%. The perforations were perforated such that the axial length T of the first non-perforated region 44 was 6 mm, the axial length A of the perforated region 41 was 44.0 mm, and the axial length B of the second non-perforated region 45 was 70.0 mm.

[0093] One of the two foils that underwent perforation processing was used as flat foil 2, and the other was used as corrugated foil 3. The foil used as corrugated foil 3 was corrugated with a channel density of 300 channels per inch. The flat foil 2 and corrugated foil 3 thus made were wound in an overlapping state to obtain a honeycomb structure with a diameter of 50 mm, a length of 120 mm, and a channel density of 300 channels per inch.

[0094] Then, a 20mm wide and 25μm thick foil solder is wound around the obtained honeycomb structure at a designated position, and the honeycomb structure is inserted into an outer cylinder 5 with a length of 120mm and a thickness of 1.5mm. BNi-5 is used as the foil solder, and SUS436L is used as the outer cylinder. After insertion, the outer diameter of the outer cylinder 5 is reduced to 53mm. Then, powder solder is applied to the obtained honeycomb structure at a designated position. BNi-5 is used as the powder solder. The bonding structure of the honeycomb structure and the bonding structure between the honeycomb structure and the outer cylinder 5 are the same as in Example 1.

[0095] Subsequently, the same vacuum heat treatment as in Example 1 was performed to obtain honeycomb cells, and then the same catalyst loading treatment as in Example 1 was performed to obtain a catalytic converter.

[0096] (Comparative Example 2)

[0097] As a comparative example 2, an opening process was performed so that the axial length T of the first non-opening region 44 in Example 1 was 2 mm, the axial length A of the opening region 41 was 44.0 mm, and the axial length B of the second non-opening region 45 was 14.0 mm, while keeping other manufacturing conditions the same as in Example 1, to obtain a catalytic converter.

[0098] (Comparative Example 3)

[0099] As a comparative example 3, an opening process was performed so that the axial length T of the first non-opening region 44 in Example 1 was 1 mm, the axial length A of the opening region 41 was 51.9 mm, and the axial length B of the second non-opening region 45 was 7.1 mm, while keeping other manufacturing conditions the same as in Example 1, to obtain a catalytic converter.

[0100] (Comparative Example 4)

[0101] As a comparative example 4, an opening process was performed so that the axial length T of the first non-opening region 44 in Example 1 was 15 mm, the axial length A of the opening region 41 was 44.0 mm, and the axial length B of the second non-opening region 45 was 1.0 mm, while keeping other manufacturing conditions the same as in Example 1, to obtain a catalytic converter.

[0102] The catalytic converters of Examples 1-4 and Comparative Examples 1-4 were subjected to engine bench-based heating and cooling cycle tests to evaluate their structural durability. The test apparatus and the catalyst loading substrate were connected via a cone. Welding was used for the connection. A 400cc single-cylinder gasoline engine was used.

[0103] The temperature mode selected is a temperature pattern in which the inlet side temperature of the gas flowing into the catalyst-supported substrate changes between 1000°C and below 100°C as the mode of the hot and cold cycle. That is, as one cycle, the hot and cold cycle consists of the following steps: a heating step in which the inlet gas temperature reaches 900°C by rotating the engine for 5 minutes from the engine stop state, approximately 30 seconds; a holding step in which the temperature (1000°C) is maintained; and a cooling step in which the engine is stopped and room temperature air is supplied for 5 minutes, thereby cooling to 100°C within approximately 60 seconds, after which room temperature air continues to flow.

[0104] After repeating the hot and cold cycle 1000 times, the honeycomb structure was observed to confirm the occurrence of cracks in the boundary area between the open area 41 and the non-open area 45. As a result, in the honeycomb structures of Comparative Examples 1 and 2, cracks occurred near the boundary between the open area 41 and the second non-open area 45. These cracks propagated radially, penetrating to the center of the honeycomb structure. Furthermore, in the first honeycomb structure 4A of Comparative Example 3, although no cracks occurred near the boundary between the open area 41 and the second non-open area 45, a defect occurred where the foil at the entrance edge was damaged due to foil gaps. In the honeycomb structure of Comparative Example 4, cracks occurred near the boundary between the open area 41 and the first non-open area 44. These cracks propagated radially, penetrating to the center of the honeycomb structure. On the other hand, in the honeycomb structures of Examples 1 to 4, no radially propagating cracks were observed. Furthermore, no defect occurred where the foil at the entrance edge was damaged due to foil gaps. As can be seen from the above, when the axial length B of the second non-opening region 45 is less than 10 mm from the outlet side edge of the first honeycomb body 4A, and the axial length T of the first non-opening region 44 is more than 2 mm and less than 10 mm from the inlet side edge of the first honeycomb body 4A, the structural durability of the catalytic converter is improved, and cracking near the boundary between the open and non-opening regions is suppressed.

[0105] Evaluation of pressure loss and purification performance

[0106] (Examples 5 to 11, Comparative Examples 5 to 6)

[0107] Next, the pressure loss and purification performance are evaluated by varying the X value (the ratio of the axial length A of the opening region 41 of the first honeycomb 4A to the sum of the axial length L1 of the first honeycomb 4A and the axial length L2 of the second honeycomb 4B).

[0108] As Examples 5 to 11 and Comparative Examples 5 and 6, catalytic converters were fabricated as follows. Two Fe-20Cr-5Al stainless steel foils with a thickness of 50 μm were perforated with holes of 1 mm in diameter. The holes were arranged in an alternating pattern, and the aperture ratio was set to 40%. The perforation was performed such that the axial length T of the first non-perforated region 41, the axial length A of the perforated region 41, and the axial length B of the second non-perforated region 45 were the values ​​shown in Table 1 for each of the examples and comparative examples. The widths of the two Fe-20Cr-5Al stainless steel foils were appropriately set to become the length L1 of the first honeycomb 4A in each example and comparative example (refer to Table 1).

[0109] One of the two foils that underwent perforation processing was used as flat foil 2, and the other was used as corrugated foil 3. The foil used as corrugated foil 3 was corrugated with a channel density of 300 channels per inch. The flat foil 2 and corrugated foil 3 thus made were wound in an overlapping state to obtain a first honeycomb 4A with a diameter of 50 mm and a channel density of 300 channels per inch.

[0110] On the other hand, a pair of flat foils and corrugated foils, both 50 μm thick and made of Fe-20Cr-5Al stainless steel without any perforation, are wound in an overlapping manner to obtain a second honeycomb 4B with a diameter of 50 mm and a channel density of 300 channels per inch. The corrugation of the corrugated foil is performed using the same method as described above. The widths of the two Fe-20Cr-5Al stainless steel foils are appropriately set such that they become the length L2 of the second honeycomb 4B in each embodiment and comparative example (refer to Table 1).

[0111] Subsequently, the same vacuum heat treatment as in Example 1 was performed to obtain honeycomb cells, and then the same catalyst loading treatment as in Example 1 was performed to obtain a catalytic converter.

[0112] As a catalytic converter used for comparison of pressure loss and purification performance (hereinafter referred to as the reference catalytic converter), a catalytic converter consisting only of a second honeycomb cell 4B with a length of 100 mm was manufactured. The manufacturing conditions of the reference catalytic converter were the same as those of Examples 5 to 11 and Comparative Examples 5 to 6, except that the first honeycomb cell 4A was not included.

[0113] Pressure loss was evaluated by measuring the pressure difference before and after the catalytic converter by flowing ambient air adjusted to a specified flow rate through the catalytic converters obtained in the various embodiments and comparative examples. In this embodiment, a flow rate of 2.5 Nm was used. 3 Pressure loss was evaluated using 20°C air at a flow rate of 1 / min. This translates to an average flow velocity of approximately 21 m / s. The pressure loss of each embodiment and comparative example was evaluated as the rate of increase in pressure loss relative to the baseline catalytic converter (hereinafter referred to as the pressure loss increase rate).

[0114] On the other hand, regarding purification performance, a model gas (a mixture of carbon monoxide, propylene, nitric oxide, oxygen, carbon dioxide, water vapor, and nitrogen) heated to 300°C was circulated at a specified flow rate (300 liters per minute under standard conditions in this embodiment) in a catalytic converter at room temperature obtained in each embodiment and comparative example. The time required until the concentration of propylene decreased by 50% (hereinafter referred to as the 50% purification time) was used as the purification performance during cold start. The concentrations of each gas constituting the model gas were set as follows: carbon monoxide, 5000 ppm; propylene, 500 ppm; nitric oxide, 500 ppm; oxygen, 4500 ppm; carbon dioxide, 14%; water vapor, 10%; and the balance being nitrogen. The purification performance (50% purification time) of each embodiment and comparative example was taken as the reciprocal of the 50% purification time, and the increase rate relative to the reciprocal of the 50% purification time in the reference catalytic converter (hereinafter referred to as the purification performance increase rate) was used for evaluation.

[0115] Purification performance and pressure loss are inversely related. As the ratio (X) of the axial length of the opening area to the sum of the axial lengths of all cells increases, pressure loss increases, but purification performance (the reciprocal of 50% purification time) also increases. Therefore, when the ratio of the increase rate of pressure loss to the increase rate of purification performance exceeds 2.5, "purification performance is not sufficiently improved compared to the increase in pressure loss" is evaluated as "×". When the ratio of the increase rate of pressure loss to the increase rate of purification performance is less than 2.5, "purification performance is sufficiently improved compared to the increase in pressure loss" is evaluated as "〇". Furthermore, when the ratio of the increase rate of pressure loss to the increase rate of purification performance is less than 2, "purification performance is more sufficiently improved compared to the increase in pressure loss" is evaluated as "◎". The evaluation results of pressure loss and purification performance are shown in Table 5.

[0116] [Table 5]

[0117] Comparative Example 5 0.21 0.06 3.29 × Example 5 0.32 0.14 2.35 〇 Example 6 0.42 0.22 1.91 ◎ Example 7 0.53 0.28 1.88 ◎ Example 8 0.63 0.33 1.89 ◎ Example 9 0.74 0.35 2.11 〇 Example 10 0.84 0.37 2.27 〇 Example 11 0.91 0.37 2.46 〇 Comparative Example 6 0.98 0.37 2.65 ×

[0118] Referring to Comparative Examples 5 and 6, when X is less than 20% and greater than 80%, the purification performance is not sufficiently improved relative to the increase in pressure loss, and is rated as "×". On the other hand, referring to Examples 5 to 11, when X is 20% or more and less than 80%, the purification performance is sufficiently improved relative to the increase in pressure loss, and is rated as "0" or better. Furthermore, referring to Examples 6 to 8, when X is 25% or more and less than 55%, the purification performance is further improved relative to the increase in pressure loss, and is rated as "◎".

[0119] <The Influence of Separation Distance D>

[0120] (Examples 12-15, Comparative Examples 7-9)

[0121] Next, the relationship between the separation distance D between the first honeycomb cell 4A and the second honeycomb cell 4B and the purification performance was investigated. Specifically, in Examples 12 to 15 and Comparative Examples 7 to 9, various changes were made to the separation distance D (refer to Table 1), and the purification performance in each example and comparative example was compared. Other manufacturing conditions were the values ​​shown in Table 1 for each example and comparative example, and the catalytic converter was obtained by manufacturing using the same method as in Example 1.

[0122] For purification performance, a model gas heated to 300°C (a mixture of carbon monoxide, propylene, nitric oxide, oxygen, carbon dioxide, water vapor, and nitrogen) was flowed into a catalytic converter at room temperature at a specified flow rate. The time required for the propylene concentration to decrease by 90% was used as the stable purification performance for evaluation. The concentrations of each gas constituting the model gas were set as follows: carbon monoxide, 5000 ppm; propylene, 500 ppm; nitric oxide, 500 ppm; oxygen, 4500 ppm; carbon dioxide, 14%; water vapor, 10%; with the balance being nitrogen. The purification performance was evaluated at a flow rate of 300 liters per minute under standard conditions. As an evaluation of purification performance, the time required for the propylene concentration to decrease by 90% (hereinafter referred to as the 90% purification time) was used as the stable purification performance for evaluation. The purification performance (90% purification time) of each embodiment and comparative example was evaluated as a ratio to the 90% purification time in Comparative Example 9. The evaluation results are shown in Table 6.

[0123] [Table 6]

[0124] Comparative Example 7 - Example 12 0.62 Example 13 0.65 Example 14 0.75 Example 15 0.85 Comparative Example 8 1 Comparative Example 9 1

[0125] Compared with Comparative Example 9 (separation distance 50 mm), even when the separation distance D was 30 mm, the 90% purification time was not improved (Comparative Example 8). On the other hand, when the separation distance D was set to 20 mm, the 90% purification time was shortened by about 15% (Example 15). When the separation distance D was set to 10 mm, the 90% purification time was shortened by about 25% (Example 14). When the separation distance D was set to 5 mm, the 90% purification time was shortened by about 35% (Example 13). When the separation distance D was set to 2 mm, the 90% purification time was shortened by about 38% (Example 12). This is considered to be because by setting the separation distance D to 20 mm or less, heat dissipation at the separation portion becomes sufficiently small.

[0126] When the separation distance D was set to 1 mm, the first honeycomb body 4A and the second honeycomb body 4B were damaged, so the 90% purification time could not be measured. This is because the foil constituting the first honeycomb body 4A was stretched, and the outlet-side edge portion of the first honeycomb body 4A came into contact with the inlet-side edge portion of the second honeycomb body 4B.

[0127] From the above, it is understood that the separation distance D needs to be set to 2 mm or more and 20 mm or less.

[0128] <Influence of the length of T>

[0129] (Examples 16 to 17)

[0130] As Example 16, as shown in Table 1, opening processing was performed such that the axial length T of the first non-opening region 44 was 2 mm, the axial length A of the opening region 41 was 44.0 mm, and the axial length B of the second non-opening region 45 was 9.0 mm, and the other manufacturing conditions were the same as those of Example 5 to obtain a catalytic converter. As Example 17, as shown in Table 1, opening processing was performed such that the axial length T of the first non-opening region 44 was 10 mm, the axial length A of the opening region 41 was 44.0 mm, and the axial length B of the second non-opening region 45 was 1.0 mm, and the other manufacturing conditions were the same as those of Example 5 to obtain a catalytic converter. Then, for the catalytic converters obtained in Example 16 and Example 17, evaluation of pressure loss and purification performance was performed by the same method as that performed for Example 5. The evaluation results of pressure loss and purification performance are shown in Table 7.

[0131] [Table 7]

[0132] Example 16 0.59 0.32 1.87 ◎ Example 17 0.59 0.28 2.09 〇

[0133] The rate of increase in pressure loss remained unchanged in Examples 16 and 17. However, in Example 16, the purification performance was improved compared to Example 17. As a result, the ratio of the rate of increase in pressure loss to the rate of increase in purification performance was rated as "◎" in Example 16 and "○" in Example 17. That is, when the axial length T of the first non-opening region 44 is shorter than the axial length B of the second non-opening region 45, the relationship between pressure loss and purification performance becomes better.

[0134] <Influence of Aperture>

[0135] (Examples 18-25, Comparative Examples 10-18)

[0136] In Examples 18-25 and Comparative Examples 10-18, the effect of changing the pore size was investigated for Examples 1-4 and Comparative Examples 1-4. In Examples 18-20 and Comparative Examples 10-12, the pore size was set to 2 mm. In Examples 21-23 and Comparative Examples 13-15, the pore size was set to 4 mm. In Examples 24-25 and Comparative Examples 16-18, the pore size was 8 mm. Other parameters were set as shown in Tables 1-4. The catalytic converter was manufactured using the same manufacturing method as in Example 1, and tests were conducted using the same method as in Example 1 to investigate the structural durability of the catalytic converter.

[0137] In the first honeycomb structure 4A of Comparative Examples 10, 13, and 16, cracks occurred near the boundary between the opening region 41 and the second non-opening region 45. These cracks propagated radially, penetrating to the center of the honeycomb structure. Furthermore, in the first honeycomb structure 4A of Comparative Examples 11, 14, and 17, although no cracks occurred near the boundary between the opening region 41 and the second non-opening region 45, a defect occurred where the foil at the entrance edge was damaged due to foil gaps. In the first honeycomb structure 4A of Comparative Examples 12, 15, and 18, cracks occurred near the boundary between the opening region 41 and the first non-opening region 44. These cracks propagated radially, penetrating to the center of the honeycomb structure. On the other hand, in the honeycomb structures of Examples 18 to 25, no radially propagating cracks were observed, and no defect occurred where the foil at the entrance edge was damaged due to foil gaps. As can be seen from the above, when the axial length B of the second non-opening region 45 is less than 10 mm from the outlet side edge of the first honeycomb body 4A, and the axial length T of the first non-opening region 44 is more than 2 mm and less than 10 mm from the inlet side edge of the first honeycomb body 4A, the structural durability of the catalytic converter is improved regardless of the pore size, and cracking near the boundary between the open and non-opening regions is suppressed.

[0138] <The Influence of Slot Ratio>

[0139] (Examples 26-31, Comparative Examples 19-24)

[0140] In Examples 26-31 and Comparative Examples 19-24, the effect of changing the aperture ratio was investigated in Examples 1-4 and Comparative Examples 1-4. In Examples 26-28 and Comparative Examples 19-21, the aperture ratio was set to 20%. In Examples 29-31 and Comparative Examples 22-24, the aperture ratio was set to 60%. Other parameters were set as shown in Tables 3 and 4. The catalytic converter was manufactured using the same manufacturing method as in Example 1, and tests were conducted using the same method as in Example 1 to investigate the structural durability of the catalytic converter.

[0141] In the first honeycomb structure 4A of Comparative Examples 19 and 22, cracks occurred near the boundary between the opening region 41 and the second non-opening region 45. These cracks propagated radially, penetrating to the center of the honeycomb structure. Furthermore, in the first honeycomb structure 4A of Comparative Examples 20 and 23, although no cracks occurred near the boundary between the opening region 41 and the second non-opening region 45, a defect occurred where the foil at the entrance edge was damaged due to foil gaps. In the first honeycomb structure 4A of Comparative Examples 21 and 24, cracks occurred near the boundary between the opening region 41 and the first non-opening region 44. These cracks propagated radially, penetrating to the center of the honeycomb structure. On the other hand, in the honeycomb structures of Examples 26 to 31, no radially propagating cracks were observed, and no defect occurred where the foil at the entrance edge was damaged due to foil gaps. As can be seen from the above, when the axial length B of the second non-opening region 45 is less than 10 mm from the outlet side edge of the first honeycomb body 4A, and the axial length T of the first non-opening region 44 is more than 2 mm and less than 10 mm from the inlet side edge of the first honeycomb body 4A, the structural durability of the catalytic converter is improved regardless of the opening ratio, and cracking near the boundary between the opening region and the non-opening region is suppressed.

[0142] <Influence of Foil Thickness and Channel Density>

[0143] (Examples 32-34, Comparative Examples 25-27)

[0144] In Examples 32-34 and Comparative Examples 25-27, the effects of changing the foil thickness and channel density were investigated for Examples 1-4 and Comparative Examples 1-4. In Examples 32-34 and Comparative Examples 25-27, the foil thickness was set to 30 μm and the channel density was set to 400 cpsi. Other parameters were set as shown in Tables 3 and 4. The catalytic converter was manufactured using the same manufacturing method as in Example 1, and the structural durability of the catalytic converter was investigated using the same method as in Example 1.

[0145] In the first honeycomb structure 4A of Comparative Example 25, cracks occurred near the boundary between the opening region 41 and the second non-opening region 45. These cracks propagated radially, penetrating to the center of the honeycomb structure. Furthermore, in the first honeycomb structure 4A of Comparative Example 26, although no cracks occurred near the boundary between the opening region 41 and the second non-opening region 45, a defect occurred where the foil at the entrance edge was damaged due to foil gaps. In the first honeycomb structure 4A of Comparative Example 27, cracks occurred near the boundary between the opening region 41 and the first non-opening region 44. These cracks propagated radially, penetrating to the center of the honeycomb structure. On the other hand, in the honeycomb structures of Examples 32 to 34, no radially propagating cracks were observed, and no defect occurred where the foil at the entrance edge was damaged due to foil gaps. As can be seen from the above, when the axial length B of the second non-opening region 45 is less than 10 mm from the outlet side edge of the first honeycomb body 4A, and the axial length T of the first non-opening region 44 is more than 2 mm and less than 10 mm from the inlet side edge of the first honeycomb body 4A, the structural durability of the catalytic converter is improved regardless of the foil thickness and channel density, and cracking near the boundary between the open and non-opening regions is suppressed.

[0146] <The Influence of Cellular Diameter and Length>

[0147] (Examples 35-37, Comparative Examples 28-30)

[0148] In Examples 35-37 and Comparative Examples 28-30, the effects of changing the diameter and length of the honeycomb cells were investigated in Examples 1-4 and Comparative Examples 1-4. In Examples 35-37 and Comparative Examples 28-30, the diameter of the first honeycomb cell 4A and the second honeycomb cell 4B was set to 80 mm, and the axial length was set to 40 mm. Other parameters were set as shown in Tables 3 and 4. The catalytic converter was manufactured using the same manufacturing method as in Example 1, and the structural durability of the catalytic converter was investigated by testing using the same method as in Example 1.

[0149] In the first honeycomb structure 4A of Comparative Example 28, cracks occurred near the boundary between the opening region 41 and the second non-opening region 45. These cracks propagated radially, penetrating to the center of the honeycomb structure. Furthermore, in the first honeycomb structure 4A of Comparative Example 29, although no cracks occurred near the boundary between the opening region 41 and the second non-opening region 45, a defect occurred where the foil at the entrance edge was damaged due to foil gaps. In the first honeycomb structure 4A of Comparative Example 30, cracks occurred near the boundary between the opening region 41 and the first non-opening region 44. These cracks propagated radially, penetrating to the center of the honeycomb structure. On the other hand, in the honeycomb structures of Examples 35 to 37, no radially propagating cracks were observed, and no defect occurred where the foil at the entrance edge was damaged due to foil gaps. As can be seen from the above, when the axial length B of the second non-opening region 45 is less than 10 mm from the outlet side edge of the first honeycomb body 4A, and the axial length T of the first non-opening region 44 is more than 2 mm and less than 10 mm from the inlet side edge of the first honeycomb body 4A, the structural durability of the catalytic converter is improved regardless of the diameter and axial length of the honeycomb body, and cracking near the boundary between the open and non-opening regions is suppressed.

Claims

1. A catalyst-supported substrate, comprising multiple honeycomb cells, for purifying vehicle exhaust gas, characterized in that, The plurality of cells are arranged in such a manner that the central axis of each cell is approximately aligned. In the plurality of honeycomb cells, the metal foil of the first honeycomb cell located closest to the exhaust gas inlet has multiple through holes formed, while the metal foil of the remaining honeycomb cells does not have through holes formed. The first honeycomb structure is axially divided into an open region with the through hole, a first non-open region extending from the exhaust gas inlet side end of the open region to the exhaust gas inlet side edge of the first honeycomb structure, and a second non-open region extending from the exhaust gas outlet side end of the open region to the exhaust gas outlet side edge of the first honeycomb structure. In this case, the first non-open region has an axial length of 2 mm or more and 10 mm or less, and the second non-open region has an axial length of 10 mm or less. Along the axial direction, the cell adjacent to the first cell is defined as the second cell. The first honeycomb and the second honeycomb are separated in the axial direction. The axial separation distance between the first honeycomb structure and the second honeycomb structure is more than 2 mm and less than 20 mm. The proportion of the axial length of the opening region to the sum of the axial lengths of the plurality of honeycomb cells is more than 20% and less than 80%.

2. The catalyst-supported substrate according to claim 1, characterized in that, The axial separation distance between the first honeycomb and the second honeycomb is greater than 2 mm and less than 10 mm.

3. The catalyst-supported substrate according to claim 1 or 2, characterized in that, The length of the second non-opening region along the axial direction is longer than the length of the first non-opening region along the axial direction.

4. A cellular unit, characterized in that, include: Catalyst-supported substrate according to any one of claims 1 to 3; as well as The outer cylinder houses the substrate for supporting the catalyst.

5. A catalytic converter, characterized in that, include: The cellular unit as described in claim 4; as well as The catalyst is supported on the plurality of honeycomb cells.

Citation Information

Patent Citations

  • Plate catalyst

    JP1980132640A

  • Exhaust gas catalyst carrier made of metal

    JP1987053744A

  • Preventive agent for tumor

    JP1990083320A

  • Integrated tandem metal catalyst bearer

    JP1993195763A

  • Metallic carrier

    JP1994320014A